Hydrate decomposition front within porous media under thermal stimulation and depressurization conditions: Macroscale to microscale - Kou, Xuan; Li, Xiao-Sen; Wang, Yi; Chen, Zhao-Yang (International Journal of Heat and Mass Transfer, 2022)
Natural gas hydrates are unstable and easily to be decomposed under warming or depressurizing condition. The complicated hydrate decomposition process is generally characterized by a moving decomposition front, yet the essence of decomposition front evolution is unclear and the evidence is lacking. In this study, X-ray computed tomography (X-CT) technology is used to reveal the dynamic process of macroscale and microscale evolution of hydrate decomposition front. The hydrate-bearing porous samples are synthesized in the high-pressure reactor and then decomposed by the thermal stimulation method and the depressurization method with X-CT scans in real time. Macroscale results show that isolated hydrates beyond the decomposition front remain undecomposed under both two decomposition conditions, indicating the oversimplification of the decomposition front as the boundary where gas hydrates are completely decomposed. Hence, the decomposition front is redefined as the boundary which divides the hydrate-bearing sediment into an interconnected zone and an isolated zone based on the interconnectivity of hydrate particles. Microscale hydrate decomposition behaviors show that, the heat transfer differences among pores, solid media, and gas hydrates under thermal stimulation condition result in the remnant of isolated hydrates beyond the outside-in moving decomposition front. The gas fugacity differences in gas phase, water layer, and dead-end pores under depressurization condition result in the remnant of isolated hydrates beyond the top-down moving decomposition front. More importantly, we found that the remnant grain-cementing hydrates could alter the thermal-hydro-mechanical-chemical (THMC) processes outside the decomposition front, and play important roles in formation stability and ecological environment by supporting the skeleton structure of hydrate-bearing sediments. These findings may provide implications and visual evidences for production efficiency improvement and environmental protection in future field tests ...